New Geopolitics – What Is Actually “New”? - Legucka, Agnieszka (The Copernicus Journal of Political Studies, 2018)
The aim of the article is to show the differences between classical and contemporary geopolitics. Geopolitics was always considering the territory as a main determinant of states development but globalization began to offer a world structured in a very different way. In the “global village” the territory is less important as it used to be. That is why modern geopoliticians have been changing the meaning of the geographical factor. About geopolitics scholars started to write, again 1. They show it in a wider perspective, as a space/place (for example “virtual space”) or imagined space/place (for example “lost homeland”) or just people’s perception (meta-geography) of the world order, different countries, politics and culture. The question raised in the article is: Can we identify a new geopolitics as new scientific approach to explore world politics or is it just derivation of the classical geopolitical concepts? Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14760